Preoperative C-reactive protein/albumin ratio and mortality of off-pump coronary artery bypass graft - Oh, Ah Ran; Kwon, Ji-Hye; Park, Jungchan; Min, Jeong-Jin; Lee, Jong-Hwan; Yoo, Seung Yeon; Lee, Dong Jae; Kim, Wooksung; Cho, Hyun Sung; Kim, Chung Su; Lee, Sangmin Maria (Frontiers in Cardiovascular Medicine, 2024)
Background We sought to investigate the prognostic value of preoperative C-reactive protein (CRP)-to-albumin ratio (CAR) for the prediction of mortality in patients undergoing off-pump coronary artery bypass grafting (OPCAB). Methods From January 2010 to August 2016, adult patients undergoing OPCAB were analyzed retrospectively. In a total of 2,082 patients, preoperative inflammatory markers including CAR, CRP, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio were recorded. Receiver operating characteristic (ROC) curves were used to determine the optimal threshold and compare the predictive values of the markers. The patients were divided into two groups according to the cut-off value of CAR, and then the outcomes were compared. The primary end point was 1-year mortality. Results During the 1-year follow-up period, 25 patients (1.2%) died after OPCAB. The area under the curve of CAR for 1-year mortality was 0.767, which was significantly higher than other inflammatory markers. According to the calculated cut-off value of 1.326, the patients were divided into two groups: 1,580 (75.9%) patients were placed in the low CAR group vs. 502 (24.1%) patients in the high CAR group. After adjustment with inverse probability weighting, high CAR was significantly associated with increased risk of 1-year mortality after OPCAB (Hazard ratio, 5.01; 95% Confidence interval, 2.01–12.50; p < 0.001). Conclusions In this study, we demonstrated that preoperative CAR was associated with 1-year mortality following OPCAB. Compared to previous inflammatory markers, CAR may offer superior predictive power for mortality in patients undergoing OPCAB. For validation of our findings, further prospective studies are needed.